Restorasi Onlay All Porcelain Pada Gigi Molar Kiri Bawah Pasca Perawatan Pulp Capping - Fani Pangabdian; Jessica Velisia Wongso (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2016)
Background: The development of technology in the field of dental restoration is expanding rapidly, especially to increase the esthetic value. Formerly a dental restoration is said to be successful if it has excellent strenghth so it will not shown any grievances, but now esthetic value is one of the cretarion of the success in the dental restoration because everyone will expect a dental restoration which has magnify esthetic value moreover can seen as the real tooth. Purpouse: To prove the succcess of all porcelain based onlay restoration by considering the esthetic value. Case : The 55 years old male patient come to the dentist with discomfort ofmadibular left molar tooth loss filling and wanted to be treated. The tooth has been filled 2 years ago and 2 weeks ago was loose. The tooth is painful when eating and drinking cold, the patient feel uncomfortable because food often comes in and hard to clean it up. There is not any complaint of spontaneous pain and patient to be filled again. Based on some examination the clinical diagnosis is reversible pulpitis. The dentist plan to do endodontic treatment with pulp vapping and make all porcelain based restoration with a good prognosis of the patient. Patientalready wear valplast denture for 2 yeas to replace 36 tooth. Case Management: Contruction all porcelain onlay restoration on molar tooth after pulp capping accompanied by attrition. After observation towards the patient within 5 years there is not any complaints in thephysically strength nor in esthetically value. Conclusion:All porcelain onlay restoration is very convenience to be used for final restoration aster pulp capping accompanied by attrition.